Variability of aortic blood flow predicts fluid responsiveness in spontaneously breathing healthy volunteers - Škulec, Roman; Čermák, Ondřej; Skalická, Hana; Kolář, Jiří (Kardiologia Polska, 2009)
BACKGROUND: Assessment of fluid responsiveness is an important topic in acute cardiology. Echocardiographic measurement of respiratory variations of aortic blood velocity in ventilated shock patients can accurately predict the effect of volume expansion. On the other hand, it remains unclear whether this respiratory variability is a common physiological reaction to hypovolaemia and whether its measurement is applicable also in spontaneously breathing patients.
Keywords: Stroke Volume; dospělí; Female; dechový objem; Adult; Respiratory Mechanics; ženské pohlaví; Hemodynamics; hemodynamika; aorta; lidé; mechanika dýchání; referenční hodnoty; krevní tlak; Tidal Volume; rychlost toku krve; Blood Flow Velocity; Male; Reference Values; tepový objem; Aorta; mužské pohlaví; Blood Pressure; Humans